2010
DOI: 10.1111/j.1461-0248.2010.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat fragmentation causes immediate and time‐delayed biodiversity loss at different trophic levels

Abstract: Intensification or abandonment of agricultural land use has led to a severe decline of semi-natural habitats across Europe. This can cause immediate loss of species but also time-delayed extinctions, known as the extinction debt. In a pan-European study of 147 fragmented grassland remnants, we found differences in the extinction debt of species from different trophic levels. Present-day species richness of long-lived vascular plant specialists was better explained by past than current landscape patterns, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
517
5
13

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 669 publications
(555 citation statements)
references
References 42 publications
20
517
5
13
Order By: Relevance
“…Such extended time-lags have indeed been observed in habitat-scale studies on vascular plants (12,18) or cryptogams (25) for which historic indicators most markedly outperformed current indicators in explaining the proportion of threatened species in our countryscale study as well (Table 3). Contrary to common expectations (10,26), however, the risks faced by taxonomic groups represented by short-lived species such as dragonflies and grasshoppers seem to reflect human impacts on the environment with a delay similar to that for plants.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Such extended time-lags have indeed been observed in habitat-scale studies on vascular plants (12,18) or cryptogams (25) for which historic indicators most markedly outperformed current indicators in explaining the proportion of threatened species in our countryscale study as well (Table 3). Contrary to common expectations (10,26), however, the risks faced by taxonomic groups represented by short-lived species such as dragonflies and grasshoppers seem to reflect human impacts on the environment with a delay similar to that for plants.…”
Section: Discussionmentioning
confidence: 57%
“…Recent empirical research has shown that, at the scale of individual habitat patches, a delayed response of species to habitat loss and fragmentation is indeed often detectable, particularly among habitat specialists (9)(10)(11). The likelihood and magnitude of extinction debt is still contentious, however (12,13), and seems to vary with the nature of environmental degradation and with the life history traits of the species concerned (14)(15)(16)(17)(18). In long-lived or less-mobile taxa (e.g., vascular plants, bryophytes, reptiles), a delayed response of populations to the deterioration and fragmentation of their habitats is especially likely and might extend over at least several decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Anthyllis vulneraria (P=0.006), Festuca lemanii (P=0.003) and Polygala comosa (P=0.021)) were significantly less represented in "new patches". (Lindborg & Eriksson 2004;Adriaens et al 2006;Helm et al 2006;Cristofoli et al 2010a;Krauss et al 2010). Little attention has been paid to the potential contribution of secondary habitat origins through time (but see Jacquemyn et al 2003;ArroyoMora et al 2004), although it may have strong implication in metatopulation functioning (Johst et al 2002;Bossuyt & Honnay 2006).…”
Section: Spatio-temporal Dynamics Of Calcareous Grasslandsmentioning
confidence: 99%
“…Europe (Krauss et al 2010). The co-existence of historical fragmented and newly created patches colonized by grassland species may therefore lead to conditions of double disequilibrium regarding species richness: extinction debt and colonization credit.…”
Section: Spatio-temporal Dynamics Of Calcareous Grasslandsmentioning
confidence: 99%